The Effect of Age of Acquisition, Socioeducational Status, and Proficiency on the Neural Processing of Second Language Speech Sounds - Archila-Suerte, Pilar (Brain Lang, 2014)
This study investigates the role of age of acquisition (AoA), socioeducational status (SES), and second language (L2) proficiency on the neural processing of L2 speech sounds. In a task of pre-attentive listening and passive viewing, Spanish-English bilinguals and a control group of English monolinguals listened to English syllables while watching a film of natural scenery. Eight regions of interest were selected from brain areas involved in speech perception and executive processes. The regions of interest were examined in 2 separate two-way ANOVA (AoA × SES; AoA × L2 proficiency). The results showed that AoA was the main variable affecting the neural response in L2 speech processing. Direct comparisons between AoA groups of equivalent SES and proficiency level enhanced the intensity and magnitude of the results. These results suggest that AoA, more than SES and proficiency level, determines which brain regions are recruited for the processing of second language speech sounds.